Synthesis of zearalenone-16-β,D-glucoside and zearalenone-16-sulfate: A tale of protecting resorcylic acid lactones for regiocontrolled conjugation - Mikula, Hannes; Weber, Julia; Svatunek, Dennis; Skrinjar, Philipp; Adam, Gerhard; Krska, Rudolf; Hametner, Christian; Fröhlich, Johannes (Beilstein Journal of Organic Chemistry, 2014)
The development of a reliable procedure for the synthesis of the 16-glucoside and 16-sulfate of the resorcylic acid lactone (RAL) type compound zearalenone is presented. Different protective group strategies were considered and applied to enable the preparation of glucosides and sulfates that are difficult to access up to now. Acetyl and p-methoxybenzyl protection led to undesired results and were shown to be inappropriate. Finally, triisopropylsilyl-protected zearalenone was successfully used as intermediate for the first synthesis of the corresponding mycotoxin glucoside and sulfate that are highly valuable as reference materials for further studies in the emerging field of masked mycotoxins. Furthermore, high stability was observed for aryl sulfates prepared as tetrabutylammonium salts. Overall, these findings should be applicable for the synthesis of similar RAL type and natural product conjugates.
Keywords: glycosylation; masked mycotoxins; resorcylic acid esters; sulfation; zearalenone

(untitled) - Winssinger, N.; Barluenga, S. (Chem. Commun., 2007)

European legislation (EC 1881/2006). Commission Regulation (EC) No 1881/2006 setting maximum levels for certain contaminants in foodstuff – consolidated version 03.12.2012 (European Community (EC))

European commission recommendation (2006/576/EC) on certain mycotoxins in animal feed – 17.08.2006. (European Community (EC))

(untitled) - Creppy, E. E. (Toxicol. Lett., 2002)

(untitled) - Sudakin, D. L. (Toxicol. Lett., 2003)

(untitled) - Krska, R.; Josephs, R. (Fresenius' J. Anal. Chem., 2001)

(untitled) - Tiemann, U.; Tomek, W.; Schneider, F.; Vanselow, J. (Reprod. Toxicol., 2003)

(untitled) - Miksicek, R. J. (J. Steroid Biochem. Mol. Biol., 1994)

(untitled) - Shier, W. T.; Shier, A. C.; Xie, W.; Mirocha, C. J. (Toxicon, 2001)

(untitled) - Berthiller, F.; Schuhmacher, R.; Adam, G.; Krska, R. (Anal. Bioanal. Chem., 2009)

(untitled) - Tran, S. T.; Smith, T. K. (Anim. Feed Sci. Technol., 2011)

(untitled) - Berthiller, F.; Crews, C.; Dall'Asta, C.; De Saeger, S.; Haesaert, G.; Karlovsky, P.; Oswald, I. P.; Seefelder, W.; Speijers, G.; Stroka, J. (Mol. Nutr. Food Res., 2013)

(untitled) - Schneweis, I.; Meyer, K.; Engelhardt, G.; Bauer, J. (J. Agric. Food Chem., 2002)

(untitled) - Grabley, S.; Gareis, M.; Böckers, W.; Thiem, J. (Synthesis, 1992)

(untitled) - Plasencia, J.; Mirocha, C. J. (Appl. Environ. Microbiol., 1991)

(untitled) - Berthiller, F.; Werner, U.; Sulyok, M.; Krska, R.; Hauser, M.-T.; Schuhmacher, R. (Food Addit. Contam., 2006)

(untitled) - Kovalsky Paris, M. P.; Schweiger, W.; Hametner, C.; Stückler, R.; Muehlbauer, G. J.; Varga, E.; Krska, R.; Berthiller, F.; Adam, G. (J. Agric. Food Chem., 2014)

(untitled) - Mikula, H.; Hametner, C.; Berthiller, E.; Warth, B.; Krska, R.; Adam, G.; Fröhlich, J. (World Mycotoxin J., 2012)

(untitled) - Mikula, H.; Weber, J.; Lexmüller, S.; Bichl, G.; Schwartz, H.; Varga, E.; Berthiller, F.; Hametner, C.; Krska, R.; Fröhlich, J. (Carbohydr. Res., 2013)

(untitled) - Mikula, H.; Sohr, B.; Skrinjar, P.; Weber, J.; Hametner, C.; Berthiller, F.; Krska, R.; Adam, G.; Fröhlich, J. (Tetrahedron Lett., 2013)

(untitled) - Bunyapaiboonsri, T.; Yoiprommarat, S.; Khonsanit, A.; Komwijit, S. (J. Nat. Prod., 2008)

(untitled) - Paraschos, S.; Magiatis, P.; Kalpoutzakis, E.; Harvala, C.; Skaltsounis, A.-L. (J. Nat. Prod., 2001)

(untitled) - Zidorn, C.; Lohwasser, U.; Pschorr, S.; Salvenmoser, D.; Ongania, K.-H.; Ellmerer, E. P.; Börner, A.; Stuppner, H. (Phytochemistry, 2005)

(untitled) - Xu, M.; Zhang, M.; Wang, D.; Yang, C.-R.; Zhang, Y.-J. (Chem. Biodiversity, 2011)

(untitled) - Morikawa, T.; Wang, L.-B.; Ninomiya, K.; Nakamura, S.; Matsuda, H.; Muraoka, O.; Wu, L.-J.; Yoshikawa, M. (Chem. Pharm. Bull., 2009)

(untitled) - Aamer, S. (Chin. J. Chem., 2005)

(untitled) - Versilovskis, A.; Huybrecht, B.; Tangni, E. K.; Pussemier, L.; De Saeger, S.; Callebaut, A. (Food Addit. Contam., 2011)

(untitled) - Muñoz, L.; Castro, J. L.; Cardelle, M.; Castedo, L.; Riguera, R. (Phytochemistry, 1989)

(untitled) - Mikula, H.; Hametner, C.; Fröhlich, J. (Synth. Commun., 2013)

(untitled) - Mydock, L. K.; Demchenko, A. V. (Org. Biomol. Chem., 2010)

(untitled) - Wegmann, B.; Schmidt, R. R. (J. Carbohydr. Chem., 1987)

(untitled) - Damager, I.; Olsen, C. E.; Møller, B. L.; Motawia, M. S. (Carbohydr. Res., 1999)

(untitled) - Motawia, M. S.; Olsen, C. E.; Enevoldsen, K.; Marcussen, J.; Møller, B. L. (Carbohydr. Res., 1995)

(untitled) - Motawia, M. S.; Olsen, C. E.; Møller, B. L.; Marcussen, J. (Carbohydr. Res., 1994)

Protective Groups in Organic Synthesis - Green, T. W.; Wuts, P. G. W. (John Wiley & Sons, Inc., 1999)

(untitled) - Ingram, L. J.; Desoky, A.; Ali, A. M.; Taylor, S. D. (J. Org. Chem., 2009)

(untitled) - Liu, Y.; Lien, I.-F. F.; Ruttgaizer, S.; Dove, P.; Taylor, S. D. (Org. Lett., 2004)